2018
DOI: 10.1556/650.2018.30787
|View full text |Cite
|
Sign up to set email alerts
|

A bélmikrobiom, a metabolikus betegségek és a hypertonia kapcsolatának irodalmi áttekintése

Abstract: Gut flora has personal characteristics for each individual, similar to the fingerprints, consisting of a special mixture of bacterial species living in the intestines, now referred to as the gut microbiome. There is a strong correlation between the loss of microbial diversity and the functional bowel disorders, obesity, type 2 diabetes and cardiovascular disease as well as many autoimmune disorders. With genetic testing of stool diversity of the gut microbiome and exact analysis of the species and phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
4
0
4
Order By: Relevance
“…Osteoarthritis is a multifactorial and slowly progressive disease, resulting in a difficult early diagnosis through radiography or plasma biochemical analysis [23]. Different studies have revealed the relationship between cardiovascular disease, obesity, type 2 diabetes, and osteoarthritis, focusing on the role of the metabolic syndrome in provoking joint and bone damage [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis is a multifactorial and slowly progressive disease, resulting in a difficult early diagnosis through radiography or plasma biochemical analysis [23]. Different studies have revealed the relationship between cardiovascular disease, obesity, type 2 diabetes, and osteoarthritis, focusing on the role of the metabolic syndrome in provoking joint and bone damage [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…22 These microbiotas are closely associated with nutrition, metabolism, immunity, and health of the host. 23 - 25 In fact, the microbiome has been referred to as the “second genome” of animals. 26 - 30 With regard to the great effect the gut microbiota exerts on the host, studying the gut microbiota of plateau zokor provides new insight into its special adaptive mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…It is a multifactorial disorder with a very complicated etiology, where the triggering factor is still a “mystery”. Recent studies, confirming an association between type 2 diabetes, cardiovascular diseases, obesity and OA, have focused on the role of the metabolic syndrome in inducing or exacerbating joint damage [6, 7]. There is some evidence showing that the linking factor between metabolic abnormalities and the OA onset could be represented by the persistence of a chronic low-grade systemic inflammation [8].…”
Section: Introductionmentioning
confidence: 99%